La Capacidad Social en Torno al Agua - David Barkin (VertigO)
Urban water management in Mexico reflects the authorities’ inability to guarantee an adequate quantity and quality of service while also protecting the ecosystems on which they depend. This problem is exacerbated by the official reluctance to encourage or even to permit social participation in the discussion of management and supervision of public services. The analysis is based on the framework of the New Culture of Water and concludes that the problems that are identified are deliberately created as part of a strategy to place water at the service of the elites and international capital while sacrificing basic social needs. This management approach is heightening social conflict and environmental problems.